A scoping review of the evidence available for the use of salons as health promotion environments, for the prevention and management of non-communicable diseases in women from different ethnic backgrounds - Kaneri, Prerana; Lima do Vale, Marjorie; Harding, Seeromanie; Molokhia, Mariam (Frontiers in Public Health, 2023)
Introduction Women from different ethnic backgrounds are disproportionately affected by non-communicable diseases (NCDs). Underpinned by the community capital they harness, hairdressers have successfully delivered NCD prevention programmes, particularly for African-American women in disadvantaged areas. Integrating community organisations and networks into existing primary care pathways can provide a sustainable process to address inequalities in access to health care. This scoping review aimed to map the evidence about interventions based in beauty salons, particularly formative research phases, including co-development, community participation, theoretical or conceptual underpinnings, as well as aspects related to training and incentivisation of salon staff, evaluation and equity. Methods The methodological framework was based on the seminal guidance of Arksey and O’Malley, using the ‘PCC’ (participants, concept, context) structure with incorporation of other relevant materials. Studies eligible for inclusion were salon-based health interventions (concept) focused on NCDs prevention (context), targeting women (participants) from different ethnic backgrounds and published in English. The searches were conducted across PubMed, Web of Science and OVID in June 2020 and updated in January 2023, with reference lists also screened. The Reach, Effectiveness, Adoption, Implementation, and Maintenance RE-AIM framework was used to explore the potential public health impact. Results 419 titles and abstracts were screened, with eight (2%) meeting the inclusion criteria, all based in the United States of America. Two used formative phases to inform intervention development, three described evidence of co-development with key stakeholders or experts within the community and five studies referred to theoretical or conceptual frameworks. Incentivisation was provided to salon staff in five of the studies, and to clients in three of the studies. Four of the investigations collated data on socioeconomic characteristics of the target population. Discussion Formative research in the scoped studies was weakly reported upon. Community participation was implicit in each of the scoped studies, yet its application varied considerably. Theoretical and conceptual frameworks were not consistently used, and there was inadequate process evaluation to ensure equitable reach and retention of targeted groups, suggesting a more concerted effort to address health equity is needed for future interventions.